Upper Echelons Theory: An Update - Hambrick, Donald C. (Academy of Management Review, 2007)
The central premise of upper echelons theory is that executives' experiences, values, and personalities greatly influence their interpretations of the situations they face and, in turn, affect their choices. At the invitation of the editor, I recap the AMR article in which the theory was originally presented (Hambrick & Mason, 1984), discuss subsequent refinements of the theory, and lay out several promising avenues for future upper echelons research.